2014
DOI: 10.1353/cpr.2014.0002
|View full text |Cite
|
Sign up to set email alerts
|

Improving Treatment for Opioid Dependence: A Perspective From the Ohio Valley Node of the NIDA Clinical Trials Network

Abstract: The Problem Rates of adoption of evidenced-based practices, including the use of medications, to treat opioid dependence are low and severely limit secondary prevention efforts to curtail the prescription drug epidemic. Purpose of Article The goal of this article is to describe how involvement in a research clinical trials network facilitated the adoption of medications to treat opioid dependence at two community-based treatment programs affiliated with the Ohio Valley Node of the National Institute on Drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In order to formulate effective community-based responses to the opioid epidemic, communities need to be aware of strategies, such as OOPPs, that have been empirically demonstrated to reduce the morbidity and mortality associated with opioid use disorders. 11,12,15,19 Our anecdotal experiences working in the area of overdose prevention in Ohio support findings from this survey regarding misconceptions about naloxone and fears about how it may be used and similar findings have been reported in other studies. 19,20 For example, one participant in this study reported that their local law enforcement officials were stating that people trade naloxone for heroin, which we suspect is unlikely given the relative street value of naloxone compared with heroin.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In order to formulate effective community-based responses to the opioid epidemic, communities need to be aware of strategies, such as OOPPs, that have been empirically demonstrated to reduce the morbidity and mortality associated with opioid use disorders. 11,12,15,19 Our anecdotal experiences working in the area of overdose prevention in Ohio support findings from this survey regarding misconceptions about naloxone and fears about how it may be used and similar findings have been reported in other studies. 19,20 For example, one participant in this study reported that their local law enforcement officials were stating that people trade naloxone for heroin, which we suspect is unlikely given the relative street value of naloxone compared with heroin.…”
Section: Discussionsupporting
confidence: 86%
“…12 Ohio was one such state. Early in the opioid epidemic community groups in Ohio struggled to implement evidence-based strategies to respond to this public health crisis 13 and understanding the barriers may inform the development of future efforts. The purpose of this study was:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation